Immersion challenge model for Flavobacterium psychrophilum infection of Atlantic salmon (Salmo salar L.) fry. Issue 11 (17th August 2022) - Macchia, Valeria; Inami, Makoto; Ramstad, Anne; Grammes, Fabian; Reeve, Andrew; Moen, Thomas; Torgersen, Jacob Seilø; Adams, Alexandra; Desbois, Andrew P.; Hoare, Rowena
Abstract: Flavobacterium psychrophilum is the causative agent of bacterial cold‐water disease (CWBD) and rainbow trout fry syndrome (RTFS), which affect salmonids. To better understand this pathogen and its interaction with the host during infection, including to support the development of resistant breeds and new vaccines and treatments, there is a pressing need for reliable and reproducible immersion challenge models that more closely mimic natural routes of infection. The aim of this present study was to evaluate a challenge model developed previously for rainbow trout for use in Atlantic salmon. First, preliminary challenges were conducted in Atlantic salmon ( n  = 120) and rainbow trout ( n  = 80) fry using two F. psychrophilum isolates collected from each fish species, respectively; fish had been pretreated with 200 mg/L hydrogen peroxide for 1 h. Thereafter, the main challenge was performed for just one F. psychrophilum isolate for each species (at 2 × 10 7  CFU/mL) but using larger cohorts (Atlantic salmon: n  = 1187; rainbow trout: n  = 2701). Survival in the main challenge was 81.2% in Atlantic salmon (21 days post‐challenge) and 45.3% in rainbow trout (31 days post‐challenge). Mortalities progressed similarly during the preliminary and main challenges for both species, demonstrating the reproducibility of this model. This is the first immersion challenge model of F. psychrophilum to be developed successfully for Atlantic salmon.